The Impact of Technology Readiness, Usefulness, and Ease of Use on AI-Based Accounting Software Adoption - Dwianto, Agus; Nur Rahman, Arif; Itsnaini Ulynnuha, Ovi; Anam, Khoirul; Mohammed Sultan Saif, Gehad (Advances in Accounting Innovation, 2024)
Objective: This study aims to examine the impact of technology readiness, perceived usefulness, and perceived ease of use on the adoption of AI-based accounting software among undergraduate accounting students in Indonesia.Methods: This study utilized quantitative research methodology and associative design to survey 359 accounting students from the Faculty of Business and Economics at several universities in Indonesia. A total of 247 participants were selected through purposive sampling. SEM-PLS was used to evaluate the data, which was collected through an online questionnaire and SmartPLS 3.0 software.Findings: The results indicate that technology readiness did not significantly influence technology adoption. However, perceived usefulness and perceived ease of use had strong positive effects. Specifically, perceived usefulness and perceived ease of use significantly predicted technology adoption, emphasizing the importance of these factors in students' willingness to adopt AI-based accounting software.Novelty: This study contributes to the literature by providing empirical evidence on the determinants of AI technology adoption in the context of accounting education, particularly in a developing country setting.Theory and Policy Implications: The results indicate that perceived benefits and simplicity of use are important factors in technology adoption, supporting the Diffusion of Innovation Theory and the Theory of Planned Behavior. Educational institutions should prioritize improving the perceived utility and user-friendliness of AI technologies by implementing tailored training programs and intuitive interfaces. This will promote greater acceptance and utilization of these technologies among students.